(untitled) (diségno, 2020)
The historical cartography is an important documentary source for the knowledge of the places. An analysis of the representations of a territory in the medium and long term makes it possible to recognize its forms and its identity characters, understand the dynamics of transformation and preserve the memory of landscapes and architecture now definitively lost. The study of the maps can lead to interesting results and offer a methodological contribution to the research if supported by a mastery of systems and tools for survey and drawing of the architecture and the territory. The use of the compass and astronomical measurements in support of a network of instrumental stations starting from the thirteenth century guide the territorial reconnais- sance and the survey of the architectures. These procedures, widely tested during the sixteenth century, in the eighteenth century can rely on more precise equipment and are subject of a process of standardization of the methods of acquisition and graphic representation. The eighteenth century’s drawings made by military engineers for the description of the stretch of Spanish coast between Santa Pola and Alicante and for the project for a new fortified settlement in the ‘Isla Plana’ offer the opportunity to apply a research path focused on the analysis of the maps scientifically repeatable in other contexts.